2019
DOI: 10.1042/bsr20182489
|View full text |Cite|
|
Sign up to set email alerts
|

Long noncoding RNA TUG1 promotes proliferation and inhibits apoptosis in multiple myeloma by inhibiting miR-29b-3p

Abstract: Background: Long non-coding RNA taurine up-regulated gene 1 (TUG1) was reportedly involved in initiation and development of several cancers. However, its function and molecular mechanisms in multiple myeloma (MM) are still unclear. The present study aimed to determine the expression status, biological function, and potential mechanisms of TUG1 in the progression of MM. Materials and methods: The expression levels of TUG1 were examined in MM samples and cell lines by real-time quantitative PCR. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Recently, increasing studies suggested that lncRNAs could function as sponges to bind to specific miRNAs to modulate downstream target gene, which were involved in many biological process [27, 28]. TUG1 was also reported to be involved in diverse human diseases by functioning as a ceRNA to sponge a variety of miRNAs such as miR-26a [13], miR-212-3p [29], and miR-29b [30]. Consistent with those reports, in this study, we found that TUG1 was associated with cell proliferation, apoptosis, invasion, and angiogenesis of trophoblast cells through sponging miR-29b, which decipher the essential role of TUG1 in the pathogenesis of PE, and as far as we know, this was the first study that reported the TUG1-regulated pathogenesis of PE by directly targeting miR-29b as a ceRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increasing studies suggested that lncRNAs could function as sponges to bind to specific miRNAs to modulate downstream target gene, which were involved in many biological process [27, 28]. TUG1 was also reported to be involved in diverse human diseases by functioning as a ceRNA to sponge a variety of miRNAs such as miR-26a [13], miR-212-3p [29], and miR-29b [30]. Consistent with those reports, in this study, we found that TUG1 was associated with cell proliferation, apoptosis, invasion, and angiogenesis of trophoblast cells through sponging miR-29b, which decipher the essential role of TUG1 in the pathogenesis of PE, and as far as we know, this was the first study that reported the TUG1-regulated pathogenesis of PE by directly targeting miR-29b as a ceRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, TUG1 promotes cancer progression through accelerating cell proliferation and inhibiting cell apoptosis (Kuang, Zhang, Hua, Dong, & Li, 2016; Li, Chen, Zhang, & Liu, 2018; Li, Zhang, Liu, & Chen, 2018). It has also been reported that TUG1 promotes multiple myeloma cell proliferation and inhibits apoptosis by suppressing miR‐29b‐3p (Liu, Wang, & Liu, 2019), and TUG1 induces cardiac hypertrophy through sponging miR‐29b‐3p (Zou, Wang, Tang, & Wen, 2019). Moreover, TUG1 promotes OC cell proliferation and invasion by regulating WNT/β‐catenin pathway (Liu, Liu et al, 2018), or regulates angiogenesis by regulating expression of LRG1 (Fan, Li, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…lncRNA turine up‐regulated gene 1 (TUG1) contributes to the photoreceptor formation and retina development and locates at chromosome band 22q12 (Young, Matsuda, & Cepko, 2005). A variety of studies demonstrated that TUG1 is highly expressed in multiple cancers, and it has been found to contribute to carcinogenesis in laryngocarcinoma (Zhuang, Liu, & Wu, 2019), osteosarcoma (Yu, Hu, et al, 2019), multiple myeloma (Liu, Wang, & Liu, 2019), pancreatic cancer (Hui et al, 2019), melanoma (Wang, Liu, Ren, Wang, & Liu, 2019), and OC (Fan, Li, et al, 2019). Previous studies have illustrated that TUG1 promotes cancer progression by regulating LRG1 secretion through modulating tumor growth factor‐β pathway (Fan, Li, et al, 2019), and by promoting cell proliferation and invasion through regulating WNT/β‐catenin pathway (Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence indicates that the aberrant expression of long non-coding RNAs (lncRNAs) are closely associated with the development and prognosis of various types of cancer, including MM [5]. Liu et al [6] reported that lncRNA TUG1 were significantly up-regulated in MM samples and cell lines, and that down-regulation of TUG1 markedly inhibited MM cell proliferation and promoted apoptosis. LncRNA Small Nucleolar RNA Host Gene 16 (SNHG16), an SNHG member, is up-regulated and functions as an oncogene in pancreatic cancer [7] and gastric cancer [8].…”
Section: Introductionmentioning
confidence: 99%